2007
DOI: 10.1128/aac.00609-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Increasing Fluoroquinolone Resistance in Streptococcus pneumoniae Isolates in Canada, 1997 to 2005

Abstract: Molecular characterization of fluoroquinolone-resistant Streptococcus pneumoniae in Canada was conducted from 1997 to 2005. Over the course of the study, 205 ciprofloxacin-resistant isolates were evaluated for ParC and GyrA quinolone resistance-determining region (QRDR) substitutions, substitutions in the full genes of ParC, ParE, and GyrA, reserpine sensitivity, and serotype and by pulsed-field gel electrophoresis. Rates of ciprofloxacin resistance of S. pneumoniae increased significantly, from less than 1% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
(19 reference statements)
2
30
0
2
Order By: Relevance
“…49,50 However, resistance to fluoroquinolones may increase in the future, and this may have an impact on treatment outcomes. 55 Administration of fluoroquinolones was associated with better treatment success among patients with severe pneumonia. The diversity in the definition of severe pneumonia among the individual trials and the use of the Pneumonia Severity Index score as a measure for severe pneumonia may limit this finding.…”
Section: Odds Ratio (95% Ci)mentioning
confidence: 99%
“…49,50 However, resistance to fluoroquinolones may increase in the future, and this may have an impact on treatment outcomes. 55 Administration of fluoroquinolones was associated with better treatment success among patients with severe pneumonia. The diversity in the definition of severe pneumonia among the individual trials and the use of the Pneumonia Severity Index score as a measure for severe pneumonia may limit this finding.…”
Section: Odds Ratio (95% Ci)mentioning
confidence: 99%
“…By PCR and sequencing (12), the first isolate showed a mutation in the QRDR of parC (Ser79Phe), and the second one had an additional gyrA mutation (Ser81Phe). These mutations are most commonly found in fluoroquinolone-resistant S. pneumoniae strains (1,18). In addition, genetic relatedness was supported by several polymorphisms identified in the QRDRs of the two isolates: Met1Leu in parC and Ile460Val in parE.…”
mentioning
confidence: 85%
“…Isolates with a single first-step parC mutation are frequently susceptible to fluoroquinolones because the MICs are at or below the Clinical and Laboratory Standards Institute (CLSI) breakpoints (4). However, a firststep parC mutation increases the likelihood of a subsequent gyrA mutation, high-level resistance, and therapeutic failure (1,18). At the same time, it has also been observed that once a parC mutation has taken place in an S. pneumoniae strain, the mutation prevention concentration (MPC) increases dramatically for all fluoroquinolones (17).…”
mentioning
confidence: 99%
“…We recently reported that ciprofloxacin resistance in Canadian S. pneumoniae isolates increased from 0.6% in 1997/1998 to 1.7% in 2000/2001 (1). In 2003, resistance rates increased significantly to 2.3% (P Ͻ 0.05) and continued to rise annually to 4.2% by 2005 (1).…”
mentioning
confidence: 98%
“…In 2003, resistance rates increased significantly to 2.3% (P Ͻ 0.05) and continued to rise annually to 4.2% by 2005 (1). The objectives of this study were to investigate the role of clonal spread in the rapid increase of ciprofloxacin resistance in S. pneumoniae in Canada since 2003 and to determine whether these isolates are genetically related to each other or to known pandemic clones.…”
mentioning
confidence: 99%